Engaging multiple stakeholders to reconcile climate, conservation and development objectives in tropical landscapes - Reed, J.; Barlow, J.; Carmenta, R.; Vianen, J. van; Sunderland, T.C.H. (Elsevier, 2019)
Achieving equitable and sustainable development that supports climate change mitigation targets and avoids biodiversity loss remains a leading, and intractable challenge in many tropical countries. Sectorial thinking – focusing on just one aspect of the problem or system – is increasingly understood to be inadequate to address linked social-ecological challenges. Holistic approaches that incorporate diverse stakeholders across scales, sectors, and knowledge systems are gaining prominence for addressing complex problems. Such ‘integrated landscape approaches’ have received renewed momentum and interest from the research, donor and practitioner communities, and have been subsumed in international conventions related to climate, biodiversity, and sustainable development. However, implementation efforts and tangible evaluation of progress continues to lag behind conceptual development. Failure of landscape approaches to adequately engage diverse stakeholders—in design, implementation and evaluation—is a contributing factor to their poor performance. Here we draw on consultation workshops, advances in the literature, and our collective experience to identify key constraints and opportunities to better engage stakeholders in tropical landscape decision-making processes. Specifically, we ask: (1) what are the key challenges related to effectively engaging multiple stakeholders in integrated landscape approaches and (2) what lessons can be learned from practitioners, and how can these lessons serve as opportunities to avoid duplicating future research efforts or repeating past perceptions of underperformance. We present our findings within three broad categories: (i) navigating complexity, (ii) overcoming siloed thinking, and (iii) incentivizing behavioral change; thus providing a useful starting point for overcoming inherent challenges associated with engaging stakeholders in landscape approaches.